2018
DOI: 10.1016/j.pbb.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the development of drug addiction in male and female animals

Abstract: An increasing emphasis has been placed on the development and use of animal models of addiction that capture defining features of human drug addiction, including escalation/binge drug use, enhanced motivation for the drug, preference for the drug over other reward options, use despite negative consequences, and enhanced drug-seeking/relapse vulnerability. The need to examine behavior in both males and females has also become apparent given evidence demonstrating that the addiction process occurs differently in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 246 publications
(400 reference statements)
6
45
0
Order By: Relevance
“…Thus the model offered the opportunity to determine potential effects of estrous phase since some prior reports indicate that cocaine and methamphetamine IVSA change significantly in female rats across the cycle, as reviewed previously (Anker and Carroll 2011; Lynch 2017). No differences in IVSA were found across estrus phases in this study whether phase was determined solely by cytology or when the analysis was restricted to only a subset of animals for which a 4-day cycle could be clearly established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the model offered the opportunity to determine potential effects of estrous phase since some prior reports indicate that cocaine and methamphetamine IVSA change significantly in female rats across the cycle, as reviewed previously (Anker and Carroll 2011; Lynch 2017). No differences in IVSA were found across estrus phases in this study whether phase was determined solely by cytology or when the analysis was restricted to only a subset of animals for which a 4-day cycle could be clearly established.…”
Section: Discussionmentioning
confidence: 99%
“…Significant main effects from these ANOVAs were further analyzed with post hoc multiple comparisons analysis using the Tukey procedure for multi-level factors and the Sidak procedure for two-level factors. Review of the relevant literature (Anker and Carroll 2011; Lynch 2017) supports the hypothesis that drug intake during estrus would be higher than during proestrus thus pre-planned comparisons of estrus versus the other phases was used as the strongest test this hypothesis. The criterion for significant results was at P < 0.05 and all analyses were conducted using Prism 7 for Windows (v. 7.03; GraphPad Software, Inc, San Diego CA).…”
Section: Methodsmentioning
confidence: 99%
“…Review of the relevant literature (Anker and Carroll 2011;Lynch 2017) supports the hypothesis that drug intake during estrus would be higher than during proestrus thus pre-planned comparisons of estrus versus the other phases was used as the strongest test this hypothesis. The criterion for significant results was at P < 0.05 and all analyses were conducted using Prism 7 for Windows (v. 7.03; GraphPad Software, Inc, San Diego CA).…”
Section: Discussionmentioning
confidence: 99%
“…Female rats were used for this study as a further test of the generality of the binge-acquisition phenomenon and to address a general dearth of information on the self-administration of α-PVP, MDPV or indeed most cathinones in female animals (Gannon et al 2017b;Hadlock et al 2011;Schindler et al 2016;Vendruscolo et al 2017;Watterson et al 2014). Female rats will self-administer more cocaine (Roth and Carroll 2004b;Smith et al 2011) and more methamphetamine (Reichel et al 2012; Carroll 2004a) than male rats (see (Anker and Carroll 2011;Lynch 2017) for reviews), however the IVSA of entactogen stimulants such as mephedrone, methylone and 3,4-methylenedioxymethamphetamine (MDMA) does not differ substantially between male and female rats . Other studies have failed to find any sex-difference in IVSA of cocaine in rats (Miller et al 2017;Perry et al 2013) or the oral self-administration of cocaine in mice (DePoy et al 2016) and in some cases male rats may acquire cocaine IVSA more rapidly and in higher proportion compared with female rats (Swalve et al 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Sex differences are also apparent in the pharmacokinetic, metabolic, and analgesic effects of oxycodone (Chan et al, 2008;Holtman and Wala, 2006;Neelakantan et al, 2015) , and subtle differences have been observed in the liability for opioid abuse (Collins et al, 2016;Mavrikaki et al, 2017) . Therefore animal studies show that, relative to males, females self-administer more opioids, are more vulnerable to their reinforcing effects, and become more physically dependent, (Alexander et al, 1978;Boyer et al, 1998;Cicero et al, 2003Cicero et al, , 2002aGraziani and Nisticò, 2016b;Hadaway et al, 1979;Lofwall et al, 2012;Lynch, 2018;Lynch et al, 2002;Serdarevic et al, 2017) . In our work presented here, when rats were given a choice between a water bottle and an oxycodone-containing bottle, both sexes readily drank oxycodone and escalated their intake, but females self-administered twice as much oxycodone by body weight as did males, with a resultant five-fold increase in blood levels.…”
Section: Oxycodone 2-bottle Choice Highlights Sex Differences In Oxycmentioning
confidence: 99%